Perencanaan Pendidikan dalam Meningkatkan Efektivitas dan Mutu Pendidikan di MTs Negeri Binjai - Hadijaya, Yusuf; Azizi, Ahmad Raihan; Monalisa , Febri Nanda; Fadla, Sarah Lailatil (IKAMAS: Manajemen Pendidikan Islam, 2022)
This study aims to examine the role educational planning in improving the effektiveness and quality of education in Madrasah Tsnawiyah. This study uses a qualitative approach. For information on this research data, the researchers took several sources of information from the Head of Madrasah at Mts Negeri Binjai. The results of the study indicate that the educational planning model applied in this madrasa is comprehensively in accordance with the educational regulations of the Ministry of Religious Education, Ministry of Religion. Then the effectiveness of the implementation of the educational planning model designed by the Madrasah Head at MTs Negeri Binjai can be seen by the achievement of the planned targets, as well as the running of the existing system, namely cooperation between each component both from the school and the committee in supporting the achievement of the educational goals set. has been planned. With the model and the effectiveness of the educational planning, it can be understood that the role of implementing the educational planning prepared by the Madrasah Head at MTs Negeri Binjai is oriented towards independent learning with a focus on 3 components of educational attainment that exist in students, namely cognitive, affective and psychomotor.